Design and Implementation of Temperature Control for a Mini-chamber using Self-Tuning PID Controller - Muhammad Aziz Muslim; M. Rony Hidayatullah (Universitas Sriwijaya, 2019)
Despite its popularity in industrial application, PID controller suffers parameters setting difficulty due to set point change, disturbance, and ageing. This paper proposed Self-tuning PID controller using Dahlin method for temperature control of a laboratory scale mini-chamber. Experimental results show that the proposed controller has better performance compared to the conventional PID controller in term of rise time and settling time. It also shows that the algorithm can compensate the changing environment and robust toward the existence of disturbance.